multiply by the formula or vice versa - to determine the polynomial multiplied.

1. (10-3y)2 = 2. (m+3) (m+3) =

3. (5x4y2)2 =
4. (m+n)2 =
5. (s-t)2 =
6. (2a+5)2 =
7. (-a+3c)2 =
8. (-5x-3y)2 =
9. c2 - 2cd + d2 =
10. (10a+2)2 =
11. (3m2 +4n) (3m + 4n) =
12. (5-x) (5-x) =
13. (x-y)2 =
14. (p+3)2 =
15. (4-3b)2 =
16. (-2a-5b)2 =
17. (-4+3m)2 =
18. m2 + 2mn + n2 =

any help would be much appreciated

Originally Posted by nataku
multiply by the formula or vice versa - to determine the polynomial multiplied.

1. (10-3y)2 = 2. (m+3) (m+3) =

3. (5x4y2)2 =
4. (m+n)2 =
5. (s-t)2 =
6. (2a+5)2 =
7. (-a+3c)2 =
8. (-5x-3y)2 =
9. c2 - 2cd + d2 =
10. (10a+2)2 =
11. (3m2 +4n) (3m + 4n) =
12. (5-x) (5-x) =
13. (x-y)2 =
14. (p+3)2 =
15. (4-3b)2 =
16. (-2a-5b)2 =
17. (-4+3m)2 =
18. m2 + 2mn + n2 =

any help would be much appreciated
All of these are based on the following formula: $\displaystyle (a + b)^2 = a^2 + 2ab + b^2$.
So for the first one we have $\displaystyle (10 - 3y)^2$. We can identify, using the above formula, that a = 10 and b = -3y. So we have $\displaystyle (10 - 3y)^2 = (10)^2 + 2(10)(-3y) + (-3y)^2$. How do you simplify this?